Development of a TOGA Pilot Garden and Diversification of Herbal Products as an Effort to Empower the Community of Dusun Munggur: Pengembangan Kebun Percontohan TOGA dan Diversifikasi Produk Herbal sebagai Upaya Pemberdayaan Masyarakat Dusun Munggur - Dini Rheynata Viony; Silfa Istiqomah; Faatimah Faatimah; Reni Andriana; Dalva Sania Azzahra; Siti Azizah Hardiningtyas (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
Dusun Munggur, Giriharjo Village, Ngrambe District, Ngawi Regency, has significant potential in medicinal plants that have been traditionally utilized in the form of herbal remedies. However, the cultivation area is relatively distant and the variety of plants grown remains limited, while productive management of household yards and product diversification has not been optimized. This Community Service Program (KKN) aimed to establish a Family Medicinal Plant (TOGA) pilot garden in an easily accessible household yard through a community-based empowerment approach. The implementation methods consisted of several stages: (1) a door-to-door  survey to identify prevalent resident diseases and to inventory existing households medicinal plants; (2) appropriate medicinal plant species identification; (3) establishment of a pilot garden and simple processed products development; and (4) socialization. The survey results indicated that gout, gastric acid disorders, and hypertension were the most common health problems. Then, the selected plants were cultivated in the pilot garden included red ginger, turmeric, white turmeric, kencur, mint, aloe vera, cat’s whiskers, gotu kola, pandan leaves, and lemongrass. The program produced tangible outputs, including a TOGA pilot garden, processed herbal products in the form of gummy jelly and golden latte, a recipe booklet for both products, as well as brochures and posters addressing gout, gastric acid disorders, hypertension, and preparation methods. Overall, the program enhanced community knowledge and skills in establishing a TOGA pilot garden and producing simple value-added herbal products, thereby optimizing the potential of household yards and promoting sustainable use of medicinal plants.